Prognostic Value of Cystatin C as a Predictor of Adverse Outcome in Severe Pneumonia Associated with COVID-19 - D. I. Korabelnikov; M. O. Magomedaliev; S. E. Khoroshilov (Общая реаниматология)
Objective. To assess the cystatin C (CysC) prognostic value for probability of death in patients with severe and extremely severe pneumonia associated with COVID-19.Material and methods. A single-center prospective study included 72 patients with severe and extremely severe pneumonia associated with COVID-19 undergoing treatment in the ICU of multifunctional medical center from September 2020 to October 2021. Recovered survivors (N=55) were analyzed as a Group 1, nonsurvivors (N=17) were considered as a Group 2.Results. The serum (s-CysC) and urine (u-CysC) CysC concentrations were significantly lower in Group 1 patients vs Group 2, averaging 1.31 mg/l vs 1.695 mg/l (P=0.013550), and 0.25 mg/l vs 0.94 mg/l (P=0.026308), respectively. Significant differences were also revealed in the subgroups differed by age (P=0.0094), platelet count (P=0.001), serum fibrinogen concentration (P=0.016), as well as CURB (P=0.02334), CRB-65 (P=0.032564), and SOFA (P=0.042042) scores. Therefore, s-CysC and u-CysC were statistically significant predictors of death in patients with pneumonia associated with severe and extremely severe COVID-19: 16.273 (95% CI: 2.503–105,814), P=0.003 and 1.281 (95% CI: 1.011–1.622), P=0.040, respectively. Urine and serum CysC were established as predictors of death in pneumonia associated with severe and extremely severe COVID-19, where u-CysC was defined as highly informative (ROC AUC 0.938 (95% CI: 0.867–1.000; P=0.000), with 90% sensitivity and specificity), and s-CysC — as informative (ROC AUC 0.863 (95%CI: 0.738–0.988; P=0.000) with 80% sensitivity and 72% specificity) predictive markers.Conclusion. Levels of S-CysC and u-CysC are of high prognostic significance and may contribute to identifying patients at a high risk of unfavorable outcome (death) due to pneumonia associated with severe and extremely severe COVID-19. Both S-CysC and u-CysC concentrations increasing up to 1.44 mg/l and 0.86 mg/l, respectively, were associated with high probability of death.